On the Uniqueness of Meromorphic Functions on Annuli in terms of Deficiencies - Dawei Meng; Nan Lu; Sanyang Liu (Journal of Function Spaces)
The purpose of this article is to study the uniqueness of meromorphic functions on annuli. Under a certain condition about deficiencies, we prove some new uniqueness theorems of meromorphic functions on the annulus A=z:1/R0<z<R0, where 1<R0≤+∞.